"Everything inside me was silenced": (Re)defining rape through visceral counterpublicity. Issue 2 (3rd April 2018) - Larson, Stephanie R.
ABSTRACT: This essay advances a theory of visceral counterpublicity through two case studies of recent high-profile rape crimes in the United States – the cases of Emily Doe and Emma Sulkowicz. Both cases garnered considerable public attention, yet neither perpetrator was convicted of rape. This essay analyzes how Doe and Sulkowicz performed public responses to these outcomes, using their bodies to argue what happened to them was indeed rape. These embodied forms constitute what I call visceral counterpublicity: modes of public engagement that (1) proceed when discursive frameworks understood through liberal subjectivity fall short; (2) expose the body's threatened boundaries to incite an affective response, or bodily intensity, in audiences; and (3) illuminate a subjugated position within the public sphere. Together, these cases call into question how mainstream publics define and discuss rape and suggest a potential shift in public opinion over rape to include visceral frameworks. This theory provides utility for rhetorical theorists and critics attempting to make sense of a range of embodied protests by drawing attention to how legal structures appear in and create larger public discourse about the body and violence.